Teratogenic effect of retinoic acid in swiss mice - Quemelo,Paulo Roberto Veiga (2007)
PURPOSE: To identify the types of malformations resulting from the administration of retinoic acid (RA) to Swiss mice on different days of pregnancy. METHODS: Twenty-four pregnant Swiss mice were divided into 4 groups of 6 animals each. The experimental groups received a single intraperitoneal injection of RA (70 mg/kg) on gestational days 7, 8 and 9 (D7, D8 and D9), while control animals (C) received only saline solution. RESULTS: Were obtained: exencephaly (C:0; D7:16.1%; D8:25.4%; D9:0), myelomeningocele (C:0; D7:25.8%, D8:30.9%, D9:0), spina bifida occulta (C:0, D7:29%, D8:41.8%, D90), gastroschisis (C:0, D7:6.4% D8:5.4%, D9:0), omphalocele (C:0, D7:6.4%, D8:14.5%, D9:0), lower limb alterations (C:0, D7:74.1%, D8:80%, D9:0), imperforated anus (C:0, D7:100%, D8:100%, D9:100%), and tail agenesis/alteration (C: D7:100%, D8:100%, D9:100%). CONCLUSION: The experimental model using Swiss mice proved to be efficient in the induction of the different types of defects, with the eighth gestational day being the one that most favored the induction of neural tube defect, omphalocele, gastroschisis, lower limb defects, imperforated anus and tail agenesis/alteration. On this basis, this is a useful model for future investigation of neural development and of the formation of the appendicular skeleton.